OPTIMASI JARINGAN 5G NEW RADIO BERDASARKAN PERFORMANSI JARINGAN 4G LONG TERM EVOLUTION DI AREA UNIVERSITAS BRAWIJAYA MALANG - Talcha Krusbeek Orrilia; Ali Mustofa; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2022)
The demand and need for network services and mobile data services are very high, which encourages the use of 5G NR technology. Currently, 5G NR technology has not been fully implemented in Indonesia. As a result, a 5G NR MHz network planning was carried out in this study based on the performance of the 4G LTE network obtained from the drive test method in the area of Brawijaya University, Malang. The coverage planning uses the cost-hatta propagation model. This propagation model is used with the consideration of flexible frequency usage, and the city of Malang is an urban area. The purpose of this study was to determine the site location mapping (gNodeB) and 5G NR network coverage at Brawijaya University Malang. So the results can be taken into consideration in planning the 5G NR network. 5G NR network planning is created by calculate the cell radius, coverage, calculate the number of sites, and mapping them on a planning tool called Atoll. Keyword : Drive Test, Optimasi, Coverage Planning, 4G LTE, 5G NR